All fall down [compact disc, unabridged] : a novel - Weiner, Jennifer (Simon & Schuster Audio, 2014)
Allison is a normal mother: until a website she develops takes off, giving her more money than she ever dreamed of, and her life starts falling apart. Allison finds that the prescription painkillers she took for a back injury help her deal with more than just a physical pain; they let her get through her increasingly hectic days. Allison then ends up in a world she never thought she'd experience outside of a movie theater: rehab.